(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes historical and modern variations of philosophical concepts related to linguistics, thinking and consciousness. The connections between language and thought, philosophical concepts of consciousness, the influence of modern science and technological developments on thinking and consciousness have been considered. The article highlights approaches aimed at understanding the interaction of language, thinking and consciousness, as well as their contribution to the development of mankind.